Teacher’s Creativity in The Vuca Era: A Systematic Literature Review Using Bibliometric Analysis - Mulyoto Mulyoto; Madhakomala Madhakomala; Rugaiyah Rugaiyah; Burmann Ulrika; Oparina Bjorn (Journal Neosantara Hybrid Learning, 2023)
In VUCA era, teachers’ creativity becomes crucial to help students overcome the surrounding rapid and complex changes. A creative teacher can create flexible, innovative, and responsive teaching methods responding to students’ needs to face the unpredictable and unstable environment. Teachers’ creativity also allows students to develop their critical, creative, and analytical way of thinking, along with teamwork and communication skill. Teacher creativity is so important that it is necessary to study how teacher creativity is viewed from the last five years research results, to provide a real understanding and follow-up in escalating teacher creativity. This systematic literature review is aimed to review research results related to the topic of teacher creativity. A systematic review protocol was designed and implemented in a systematic literature search procedure that was carried out on three data-based electronic platforms namely Sciencedirect, Emerald, and Springer Link. The literature selection protocol used the PRISMA method. The results of the literature study showed that the last five years’ research on teacher creativity is related to technology, STEAM, self-efficacy, educational environment, creative disposition, creative thinking, student motivation, and interest. Collaboration from related parties is needed in creating teachers who are creative in teaching. Teachers must be open to technological developments and leaders of educational institutions must be able to create a creative and innovative environment so that teachers can confidently develop their creativity which will effectively create challenging and innovative learning experiences for students.